1H NMR spectra. Part 29§: proton chemical shifts and couplings in esters—the conformational analysis of methyl γ‐butyrolactones. (5th November 2012) - Abraham, Raymond J.; Leonard, Paul
Abstract : The 1 H NMR spectra of 35 cyclic and acyclic esters are analysed to give the 1 H chemical shifts and couplings. The substituent chemical shifts of the ester group were analysed using three‐bond ( γ ) effects for near protons and the electric field, magnetic anisotropy and steric effect of the ester group for more distant protons. The electric field is calculated from the partial atomic charges on the O⋅C = O atoms, and the asymmetric magnetic anisotropy of the carbonyl group acts at the midpoint of the C = O bond. The values of the anisotropies Δ χ parl and Δ χ perp were for the aliphatic esters 10.35 and −18.84 and for the conjugated esters 7.33 and −15.75 (×10 −6 Å 3 /molecule). The oxygen steric coefficients found were 104.4 (aliphatic C = O), 45.5 (aromatic C = O) and 16.0 (C–O) (×10 −6 Å 6 /molecule). After parameterisation, the overall RMS error for the data set of 280 entries was 0.079 ppm. The strongly coupled 1 H NMR spectra of the 2‐methyl, 3‐methyl and 4‐methyl γ‐butyrolactones were analysed and the methyl conformational equilibrium obtained from the observed couplings. The observed versus calculated density functional theory (DFT) ΔG(ax‐eq) was 1.0 (1.01), 0.34 (0.54) and 0.65 (0.71) kcal/mol res. The shielding effect of a methyl cis to a proton in the five‐membered lactone rings is −0.40 ±0.05 ppm and deshielding trans effect 0.12 ±0.05 ppm, which is common to both five and six membered rings. The cis / trans isomerism in the vinyl esters methyl acrylate, crotonate and methacrylate and methyl furoate was examined using the 1 H chemical shifts. The calculated shifts of both the cis and trans isomers were in good agreement with the observed shifts. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : The 1 H spectra of 35 esters are analysed and their 1 H shifts reproduced by a semi‐empirical model. The conformer equilibria of the three methyl g‐butyrolactones were obtained from the observed HH coupings. DG(ax‐eq) values of 1.0, 0.34 and 0.65 kcal/mol were found for the 2, 3 and 4 methyl compounds res.